2022
DOI: 10.4250/jcvi.2022.0003
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Cardiac Magnetic Resonance Imaging Detects Altered Myocardial Tissue and Function in Heart Transplantation Recipients Monitored for Cardiac Allograft Vasculopathy

Abstract: BACKGROUND Cardiac allograft vasculopathy (CAV) is a complication beyond the first-year post-heart transplantation (HTx). We aimed to test the utility of cardiac magnetic resonance (CMR) to detect functional/structural changes in HTx recipients with CAV. METHODS Seventy-seven prospectively recruited HTx recipients beyond the first-year post-HTx and 18 healthy controls underwent CMR, including cine imaging of ventricular function and T1- and T2-mapping to assess myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Cardiac magnetic resonance imaging (CMR) is a non-invasive imaging modality that can provide comprehensive information about the structure and function of the heart that is relevant for the diagnosis and prognosis of CAV ( Figure 3 ) [ 8 ]. CMR can provide information about structural changes by measuring parameters such as extracellular volume (ECV) fraction, fibrosis, and edema [ 58 ]. However, functional parameters such as myocardial perfusion reserve (MPR), diastolic strain (DS) rate by CMR, and peak filling rate (PFR) carry more importance for CAV diagnosis, as most studies using CMR have focused on MPI and strain imaging [ 59 , 60 ].…”
Section: Non-invasive Modalitiesmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging (CMR) is a non-invasive imaging modality that can provide comprehensive information about the structure and function of the heart that is relevant for the diagnosis and prognosis of CAV ( Figure 3 ) [ 8 ]. CMR can provide information about structural changes by measuring parameters such as extracellular volume (ECV) fraction, fibrosis, and edema [ 58 ]. However, functional parameters such as myocardial perfusion reserve (MPR), diastolic strain (DS) rate by CMR, and peak filling rate (PFR) carry more importance for CAV diagnosis, as most studies using CMR have focused on MPI and strain imaging [ 59 , 60 ].…”
Section: Non-invasive Modalitiesmentioning
confidence: 99%
“…Although several studies have shown that elevated native T1, T2, and extracellular volume fraction (ECV) may be markers of acute rejection, 10) 11) few studies have focused on the relationships between these parameters and CAV. In this issue of Journal of Cardiovascular Imaging , Abbasi and colleagues 12) demonstrated structural (T1, T2, and ECV values) and functional parameters of CMR in patients monitored for CAV beyond the first-year post heart transplantation. The study included 77 heart transplantation recipients and 18 matched controls who underwent CMR.…”
mentioning
confidence: 98%